El inventario de mercaderías y su relación con el cumplimiento de la norma NIIF pymes 10103 en la empresa " La casa del dulce", cantón Quevedo, año 2013 - Mora Zúñiga, Wilson Andrés (2013)
Inventory of goods and their relation to the implementation of IFRS SMEs 10103 standard, the company “La Casa del Dulce”, was carried out in Quevedo town, in 2013. Its main objective was to examine the process of adoption of inventory management under IFRS SMEs 10103 standard in the business. Specifically, the research aimed to examine the inventory valuation under IFRS SMEs 10103 standard, measuring the value of inventory impairment under IFRS SMEs 10103 standard and analyze the costing formula to be used in the company under the standard IFRS SMEs 10103. The hypothesis proposed was: Consideration for inventory will demonstrate the level of compliance with IFRS’s SMEs 10103. The investigation found that the review of inventory valuation under IFRS SMEs 10103 standard was evident that the company “La Casa del Dulce" includes all costs of purchase, costs of conversion and other costs incurred in bringing the current condition and location inventories. Therefore, valuation of inventories of the company " La Casa del Dulce" follows the guidelines of section 13.4 of the Standard IFRS SMEs 10103 , Inventories. With regard to the measurement of the value of inventory deterioration, the present investigation found that the company “La Casa del Dulce" does not report whether any inventories are impaired (in breach of the guidelines of Clause 13.19 of the Standard IFRS SMEs 10103, Inventories). Analyzing of the costing formula used by the company under IFRS SMEs 10103 norm, showed that the company “La Casa del Dulce " uses the formula of last -in, first -out (LIFO ) method to measure the cost of inventories to calculate the cost. Consequently, inventory costing the company "La Casa del Dulce" does not meet the guidelines of Clause 13.17 of the Standard IFRS SMEs 10103, Inventories. The last entry method first out (LIFO) is not allowed in this IFRS. This technique prevents rotation of inventory. In measuring the value of deteriorating inventory under IFRS SMEs 10103 standard , the company " La Casa del Dulce" does not report whether any inventories are impaired , i.e., if the carrying amount is not fully recoverable ( for example, damage, obsolescence or declining selling prices ). Considering the value of impairment of inventories of the company “La Casa del Dulce" does not meet the guidelines of Clause 13.19 of the Standard IFRS SMEs 10103, Inventories.